Композитні кріогелі, наповнені наноструктурованими матеріалами: досягнення та перспективи - Діхтярук, Є. В. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2025)
The article presents a review of the current state of synthesis and applications of composite cryogels prepared using cryotropic gelation and incorporating nanostructured materials. Particular attention is paid to poly(vinyl alcohol) (PVA) and chitosan as key biocompatible polymer matrices. The fundamental principles of cryotropic gelation, such as freezing and the factors influencing the formation of the macroporous cryogel structure, are analyzed, including temperature and freezing rate, number of freeze–thaw cycles, solution composition, type of cross-linking, presence of electrolytes and low-molecular weight additives. The features of physically and chemically cross-linked hydrogels are discussed along with mechanisms of pore formation, cryoconcentration, phase separation, and intermolecular bonding. Modern approaches to composite cryogel synthesis are examined, particularly in situ and ex situ methods of nanofiller incorporation (carbon nanotubes, metal oxides, clays, etc.), and their effects on the morphology, mechanical properties, and bioactivity. Special attention is given to the biomedical applications of cryogels, including drug delivery, implants, tissue scaffolds, and antibacterial or hemostatic coatings. In vitro and in vivo characteristics are addressed, including biodegradability, release control, cytocompatibility, and mechanical stability. The combination of PVA and chitosan in composite cryogels provides an optimal balance between elasticity, bioactivity, and sorption capacity. The article summarizes the literature of the last two decades and identifies future development directions, especially the design of smart cryogels with integrated functions for biomedical applications.